Penerapan problem-based learning (pbl) dengan pendekatan tri-nga untuk membangun passion mahasiswa calon guru kejuruan - Siti Mariah; Setuju Setuju; Heri Maria Zulfiati; Enggar Kartikasari (Universitas Sarjanawiyata Tamansiswa, 2020)
This classroom action research is motivated by the condition of the pre-research that shows students are lacking self-confidence and lack of enthusiasm in participating in educational learning with a teacher center approach. This study aims to introduce Problem-based learning with the Tri-Nga (Ngerti-Ngrasa-Nglakoni) approach to increase student passion to be ready to become vocational teachers. The study uses the Kemmis Taggart model with 2 cycles consisting of planning, implementation, and reflection. Study material for the first cycle of direct instruction and the second cycle of indirect instruction. The research subjects were 29 students of PKK study program in semester 3 of 2019-2020 academic class A in the FKIP UST. Data collection techniques through observation and interviews were analyzed descriptively. The results showed an increase in student passion shown by the aspects of understanding, feeling, and nglakoni which increased significantly. Students can understand the knowledge, attitudes, and skills that must be possessed by vocational teachers by analyzing learning problems in vocational schools, best practice, and reviewing instructional videos, students can appreciate the teaching profession through the study of various learning methods, and students practice learning through teaching simulations.